1980
DOI: 10.1159/000194226
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bromhexine Metabolite VIII (NA 872) and Bromhexine-Glucose in Treatment of Adult Respiratory Distress Syndrome

Abstract: The authors study the changes in cardiopulmonary function after application of bromhexine metabolite VIII (NA 872) in an animal model of adult respiratory distress syndrome (ARDS) and bromhexine glucose solution (BGS) in ARDS patients. After damage of the lung alveolar surfactant by intratracheal atomization of 0.2 M HC1 in LEWE Minipigs significant changes in lung compliance, dead space ventilation, venous admixture, alveolo-arterial oxygen tension difference, pulmonary vascular resistance, and oxygen uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In an animal model, or in ARDS patients, the administration of bromhexine metabolite VIII or bromhexine glucose solution, respectively, significantly reverses the compliance decrease and otherwise improves the respiratory functions of the lung. 46 Further work along these lines can be expected and may someday involve the intratracheal instillation of synthetic or natural surfactants which have been used successfully in infants with respiratory distress to improve lung compliance and expand alveoli. 47 While heparin has been used to reduce the incidence of thrombus formation in ARDS, 48 promising new data show that streptokinase fibrinolysis may also be effective.…”
Section: Pharmacology Of Ardsmentioning
confidence: 99%
“…In an animal model, or in ARDS patients, the administration of bromhexine metabolite VIII or bromhexine glucose solution, respectively, significantly reverses the compliance decrease and otherwise improves the respiratory functions of the lung. 46 Further work along these lines can be expected and may someday involve the intratracheal instillation of synthetic or natural surfactants which have been used successfully in infants with respiratory distress to improve lung compliance and expand alveoli. 47 While heparin has been used to reduce the incidence of thrombus formation in ARDS, 48 promising new data show that streptokinase fibrinolysis may also be effective.…”
Section: Pharmacology Of Ardsmentioning
confidence: 99%
“…According to a study conducted by Cataldi et al on the effect of bromhexine metabolites in children with respiratory disorders, the positive effect of this drug was observed in the treatment of sputum caused by respiratory infections (9). The administration of bromhexine in treatment of adult respiratory distress syndrome (ARDS) was investigated in a study by Kuckelt et al, which showed in patients with ARDS who were treated with bromhexine, pulmonary function is significantly ameliorated (10).…”
mentioning
confidence: 99%